Proceedings IEEE Conference on Computer Vision and Pattern Recognition. CVPR 2000 (Cat. No.PR00662)
DOI: 10.1109/cvpr.2000.854890
|View full text |Cite
|
Sign up to set email alerts
|

A generalized optical flow constraint and its physical interpretation

Abstract: This paper addresses the issue of motion estimation on image sequences. The standard motion equation used to compute the apparent motion of image irradiance patterns is an invariance brightness based hypothesis called the optical flow constraint. Other equations can be used, in particular the extended optical flow constraint, which is a variant of the optical flow constraint, inspired by the fluid mechanic mass conservation principle. In this paper, we propose a physical interpretation of this extended optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 14 publications
0
52
0
1
Order By: Relevance
“…The first assumption is difficult to validate, especially in meteorological images due to the complexity and the heterogeneity of the underlying physical processes. Nevertheless, as shown by several works, the use of the continuity equation in the case of meteorological data is appealing [4,24]. As the brightness consistancy is obviously not verified in that type of images, the equation of continuity provides us with an interesting alternative data-model.…”
Section: Continuity Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…The first assumption is difficult to validate, especially in meteorological images due to the complexity and the heterogeneity of the underlying physical processes. Nevertheless, as shown by several works, the use of the continuity equation in the case of meteorological data is appealing [4,24]. As the brightness consistancy is obviously not verified in that type of images, the equation of continuity provides us with an interesting alternative data-model.…”
Section: Continuity Equationmentioning
confidence: 99%
“…The continuity equation originally introduced in [20] as a data model for motion estimation of intensity time varying images has been since incorporated in several works. It has been considered in the context of fluid imagery either for satellite meteorological images [4,7,24] or for experimental fluid mechanics [23]. It has also been introduced in medical imaging domain to recover 3D deformation fields of the heart [21] or to analyze blood flow [1].…”
Section: Continuity Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Neglecting mass exchanges via vertical motion on planar integral boundaries, in [11] and [2], the authors demonstrated that the integration of (3) leads to a mass-conservation model called ICE…”
Section: ) Integrated Continuity Equation (Ice)mentioning
confidence: 99%
“…The problem of motion estimation from image sequences has been extensively studied [5,6,7,8,9,10,11,12,13]. The classical computer vision approach relies on a dense estimation of the displacement velocity based on the so-called conservation of gray level-value assumption (also called optical flow constraint): given a pixel (x(t), y(t)) on an image I at time t, we have:…”
Section: Objectivesmentioning
confidence: 99%